1996
DOI: 10.1093/ndt/11.6.1079
|View full text |Cite
|
Sign up to set email alerts
|

Regular low-dose intravenous iron therapy improves response to erythropoietin in haemodialysis patients

Abstract: Regular intravenous iron supplementation in haemodialysis patients improves the response to Epo therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 4 publications
0
45
0
Order By: Relevance
“…Several attempts to maintain the hematocrit value by administering iron preparations and to decrease the consumption volume of erythropoietin preparations have been made from the pharmacoeconomic viewpoint in U.S.A. and Europe. [8][9][10] Most recently, even in Japan, a physicians' research group has reported that a small dose of iron preparations resulted in a 30% reduction of erythropoietin consumption for one year in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to maintain the hematocrit value by administering iron preparations and to decrease the consumption volume of erythropoietin preparations have been made from the pharmacoeconomic viewpoint in U.S.A. and Europe. [8][9][10] Most recently, even in Japan, a physicians' research group has reported that a small dose of iron preparations resulted in a 30% reduction of erythropoietin consumption for one year in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The number of sideroblasts, nucleated erythrocyte precursors that stain for iron with Prussian blue, is decreased in AI 12, again suggesting iron restriction. As a further indication of the limiting role of iron in patients with AI but no evidence of iron deficiency, the resistance of AI to erythropoietin therapy can sometimes be overcome by the co-administration of parenteral iron 17,18. The mechanism by which high doses of intravenous iron preparations ameliorate resistance to pharmacologic doses of erythropoietin19, even in situations where ferritin is elevated20,21, is not yet clear.…”
Section: Iron Restriction Is a Major Contributor To Anemia Of Inflammmentioning
confidence: 99%
“…Intravenous iron supplementation is superior to oral iron in the maintenance of iron stores during EPO therapy [28][29][30]. The effectiveness of oral iron is limited by patient non-compliance, gastrointestinal side-effects and interaction with other oral medication.…”
Section: Discussionmentioning
confidence: 99%